Peranan Pengembangan Sumber Daya Manusia Dalam Meningkatkan Produktifitas Kerja Pegawai Pada Kantor Dinas Sosial Kabupaten Mojokerto - Ramadoni, Wahyu; Saputri, Dini (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
In general, this study aims to describe and analyze the development of human resources at the Mojokerto district social service office. This research is in the form of a qualitative case study or cese study. The research focus is based on the implementation of training and education in increasing employee productivity. Data collection instruments are interviews, observations at the research site and also based on documents. The length of the research is one month, the data analysis in this study was carried out qualitatively and quantitatively with the correlation coefficient formulaThe results show that Human Resource Development at the Mojokerto Regency Social Service Office is effective and optimal, this is evident in the increase in the work of employees who attend education and training every year.